An Analysis of Students’ Scientific Literacy Ability on Vibration and Wave Materials - Umi Kalsum; Tomo Djudin; Erwina Oktavianty (Universitas Lambung Mangkurat, 2023)
This study aims to describe students' scientific literacy skills on vibration and wave material at SMP Negeri 14 Pontianak and examine differences in abilities in each aspect of scientific literacy. The research method used is described with a quantitative approach. The research instrument was used in the form of test questions in the form of essays consisting of 15 questions based on scientific literacy. The sample in this study was class IX students at SMP Negeri 14 Pontianak, totalling 174 people. The measured scientific literacy includes aspects of science content, scientific processes, and the context of science. The results of data analysis showed that the scientific literacy ability of students of vibration and wave material was 33.70% for the science content aspect, 44.60% for the science process aspect, and 42.00% for the science context aspect. Based on the Kruskall-Wallis test, the results of the analysis showed that there were differences in the abilities of students in every aspect of scientific literacy. It is hoped that other researchers can apply science learning that focuses on aspects of science content.